2010
DOI: 10.1002/tea.20387
|View full text |Cite
|
Sign up to set email alerts
|

Engaging students in environmental research projects: Perceptions of fluency with innovative technologies and levels of scientific inquiry abilities

Abstract: The purpose of this mixed‐method study was to investigate the changes in high school students' perceptions of fluency with innovative technologies (IT) and the levels of students' scientific inquiry abilities as a result of engaging students in long‐term scientific research projects focusing on community‐based environmental issues. Over a span of 3 years, a total of 125 ninth‐ through twelfth‐grade students participated in this study. A project‐specific Likert‐scale survey consisting of three parts (fluency wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 32 publications
0
49
0
2
Order By: Relevance
“…In the case of a virtual laboratory with Kinect sensor technology, the implementation of NUI assists in teaching chemistry is especially successful being conducting chemical experiments. Based on this research, it can be concluded that the use of innovative technologies (Calik 2013;Ebenezer et al 2011Ebenezer et al , 2012Xie and Reider 2013), an example of which is NUI, is justified by bringing positive results in teaching. The virtual chemical laboratory with the Kinect sensor is an educational program, but may as well serve as a Serious Game.…”
Section: Summing Upmentioning
confidence: 91%
See 1 more Smart Citation
“…In the case of a virtual laboratory with Kinect sensor technology, the implementation of NUI assists in teaching chemistry is especially successful being conducting chemical experiments. Based on this research, it can be concluded that the use of innovative technologies (Calik 2013;Ebenezer et al 2011Ebenezer et al , 2012Xie and Reider 2013), an example of which is NUI, is justified by bringing positive results in teaching. The virtual chemical laboratory with the Kinect sensor is an educational program, but may as well serve as a Serious Game.…”
Section: Summing Upmentioning
confidence: 91%
“…You can highlight five areas in which different features and capabilities of ICT are used: scientific texts and lectures, cooperation and scientific discussion; representation and data collection, scientific simulation, and, finally, modeling (Linn 2003). Depending on the context of the use of ICT technology, these various expressions are used: information technology (Xie and Reider 2013), information and communication technology (Linn 2003), technology of learning (Atwater 2000;Krajcik 2002), new technologies (Krajcik et al 2000) and innovative technologies (Calik 2013;Ebenezer et al 2011Ebenezer et al , 2012Xie and Reider 2013). ICT technology, regardless of the name, may help students and teachers to broaden their thinking horizons, better mutual communication of one another, a better understanding of scientific phenomena and conducting investigations to carry scientific research (Edelson 1998;Krajcik 2002;Zhang 2013).…”
Section: Introductionmentioning
confidence: 99%
“…An explicit definition of a research question is only given in the study by White and Frederiksen (1998) where students should formulate 'a well-formed, investigable research question whose pursuit will advance their understanding of a topic they are curious about' (p. 10). Other studies mainly focus on one of the two characteristics, respectively, the need for research questions to be testable ebenezer, kaya, & ebenezer, 2011) or their potential to advance understanding (Cavagnetto, Hand, & Norton-Meier, 2010). A third characteristic is eventually addressed in a study by Samarapungavan, Patrick and Mantzicopoulos (2011) who focus on students' ability to use science concepts in the generation of scientific research questions.…”
Section: Identifying Research Questionsmentioning
confidence: 99%
“…The underlying assumption of concept mapping is that learners' existing knowledge system is like a conceptual map; as learners relate or assimilate the new knowledge/concepts into their existing knowledge system, they are actively building a conceptual relationship and the new learning becomes meaningful (Novak and Cañas, 2008). Using concept mapping to construct models has been found to be very useful in scientific inquiry (Ebenezer et al, 2011). Furthermore, students who actively seek the underlying structures (of study materials) that made sense to them were found to have better academic performance (Yang and Bliss, 2014).…”
Section: Rationalementioning
confidence: 99%